Non-coding RNAs in Pancreatic Ductal Adenocarcinoma - Gong, Ruining; Jiang, Yueping (Frontiers in Oncology, 2020)
Non-coding RNAs (ncRNAs) are reported to be expressed in human cancer, including pancreatic ductal adenocarcinoma (PDAC). They affect the growth, migration and invasion of tumor cells by regulating cell cycle and apoptosis, as well as play an important role on epigenetic modification, transcription and post-transcriptional regulation. However, whether ncRNAs alteration results in PDAC remains largely unknown. Because of this, analysis based on existing data on ncRNAs, which are crucial for modulating pancreatic tumorigenesis, will be important for the future research on PDAC. We identify non-coding RNAs with tumor-promoting function: HOTAIR, HOTTIP, MALAT1, lncRNA H19, lncRNA PVT1, circ-RNA ciRS-7, circ-0030235, circ-RNA_100782, circ-LDLRAD3, circ-0007534, circRHOT1, circZMYM2, circ-IARS, circ-RNA PDE8A, miR-21, miR-155, miR-221/222, miR-196b, miR-10a. While others including GAS5, MEG3 and lncRNA ENST00000480739, has_circ_0001649, miR-34a, miR-100, miR-217, miR-143 inhibit the proliferation and invasion of PDAC. Hence, we summarized the function of ncRNAs’ role in the occurrence, development and metastasis of PDAC, aiming to provide guidance for the clinical diagnosis and treatment of PDAC.